Chapter 16 Viking camps, an economic interpretation - Ögren, Anders (Taylor & Francis, 2023)
In this chapter I employ the formal economic theoretical framework known as New Institutional Economics (NIE) to analyse the Viking camps. This framework implies that I assume individual agents to act rationally in its bounded sense and that there exists a set of rules (formal and informal) that are monitored and enforced. My main questions are 1) why did the emerge, 2) why were they placed in these specific sites? 3) how could they have been organized economically, i.e. internally with labour specialization of goods and services, and externally in exchanges outside of the camps. 4) what roles did the identity of the camps (and their inhabitants) play? 5) what rules may have existed and how were they monitored and enforced? To do so I draw on existing literature in archaeology and ancient history on the Viking phenomenon and more specifically Viking camps.